Values, motivation, and physical activity among Chinese sport sciences students - Yan Liang; Olivier Rascle; Jian Yang; Nicolas Souchon (PLoS ONE, 2025)
Different studies have shown that values and motivation predict physical activity, but no study has tested how values and motivation may interact to predict physical activity. Specifically, the present research aimed to test how values and motivation toward physical activity measured within the SDT could predict global physical activity among Chinese sports science students. The indirect effects of openness to change and self-transcendence values on predicting physical activity through autonomous motivation were significant. These results help us understand how highly abstract psychological constructs such as values may influence physical activity through motivation. Studying values combined with motivation may help better understand the factors that motivate or inhibit physical activity.